Analisis Kawasan Usaha Pengembangbiakan dan Penggemukan Sapi Potong Berbasis Sumberdaya Lokal Pedesaan untuk Program Nasional Percepatan Pencapaian Swasembada Daging Sapi - Akhmad Sodiq (Agricultural Faculty, 2011)
Analysis of livestock estate of village breeding centre (VBC) and village fattening centre (VFC) for beef cattle based on local resources to support national program of cattle meat self-sufficiencyABSTRACT. The main focus of this study were (1) documenting the profile of livestock estate of Village Breeding Centre (VBC) and Village Fattening Centre (VFC) for beef cattle under local resources base, (2) documenting the profile of local resources in terms of the potential of individual farmer and group dynamic, (3) documenting the degree of livestock estate consist of: elementary, middle and advance. Livestock On-Farm Trials was conducted by survey on Village Breeding Centre and Village Fattening Centre. 81 VBC and VFC located at 5 regencies in Central Java (Cilacap, Banyumas, Purbalingga, Banjarnegara, and Kebumen) were involved in this study. Qualitative and quantitative descriptive statistics were applied in this study. Conclusions remark of this study: (1) The profile of livestock estate for breeding were dominated by secondary grade (92%), followed by elementary (4%) and advance (4%) grades. The profile of livestock estate for fattening better than breeding estate, the grade of livestock estate for breeding was advance (18%) and secondary (82%) and no elementary grade.; (2) The potencial of individual farmer under midle grade (77%) and high grade (23%). These good conditions are really support for developing breeding and fattening beef calte estate; (3) The poteny of group farmer institution comprise of the potency of social resources and group dynamic. The potency of social resources was dominated (85%) by high grade, followed by midle grade (15%). The good condition of social resources potency are really support livestock esate development, unfortunalty this condition unsupported by group dynamic where they are tend to be statis and decline (76%); (4) Based on the development process, beef cattle estate consists of three categories: elementary, secondary, and advance degree. Only 4% of elementary degree was found at beef cattle breeding. Mostly, they are under condition of secondary grade (92% at breeding centre, and 82% at fattening centre). The advance grade was found in small number (at breeding and fattening centre were 4 and 18%, respectively).